Sleep, circadian rhythms, and schizophrenia: where we are and where we need to go. Issue 3 (May 2018) - Cosgrave, Jan; Wulff, Katharina; Gehrman, Philip
Abstract : Purpose of review: The review is designed to give an overview of the latest developments in research exploring the relationship between sleep and psychosis, with particular attention paid to the evidence for a causal relationship between the two. Recent findings: The most interesting avenues currently in pursuit are focused upon sleep spindle deficits which may hallmark an endophenotype; explorations of the continuum of psychotic experiences, and experimental manipulations to explore the evidence for bidirectional causality; inflammatory markers, psychosis and sleep disturbances and finally, treatment approaches for sleep in psychosis and the subsequent impact on positive experiences. Summary: Globally, large surveys and tightly controlled sleep deprivation or manipulation experiments provide good evidence for a cause-and-effect relationship between sleep and subclinical psychotic experiences. The evidence for cause-and-effect using a interventionist-causal model is more ambiguous; it would appear treating insomnia improves psychotic experiences in an insomnia cohort but not in a cohort with schizophrenia. This advocates the necessity for mechanism-driven research with dimensional approaches and in depth phenotyping of circadian clock-driven processes and sleep regulating functions. Such an approach would lead to greater insight into the dynamics of sleep changes in healthy and acute psychosis brain states.